What’s to lose? A sensuous geography of renters’ bushfire experiences in Australia - Yildiz, Deniz (Frontiers in Communication, 2025)
This community case study explores the experiences of renters in Hobart, Australia’s most bushfire-prone capital, to understand how they live with and prepare for bushfire risk. Renters, a growing but often overlooked population, face distinct challenges, including limited property rights and communication that rarely reflects their circumstances. The study drew on arts-based workshops and follow-up surveys, guided by principles of disaster justice. Findings show that renters identified a series of anchors that sustained their sense of security in the face of bushfire risk. These anchors included tenure-related conditions that shaped perceptions of risk and capacity to act, sensory cues such as the smell of bushland that offered familiarity, ecological ties that connected people to land and more-than-human life, and social ties that reinforced belonging. Bushfire risk unsettled these anchors, disrupting routines and relationships that supported stability. Attending to these lived experiences highlights how preparedness strategies can be made more relevant to renters and support more inclusive approaches to bushfire readiness.